2020
DOI: 10.32598/jccnc.6.4.341.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Schema Therapy and Emotional Self-Regulation Therapy in the Components of Women’s Marital Conflicts

Abstract: Background: Marital conflicts partly happen due to the psychological disorders of couples, issues related to children, and the long periods of depression, all of which may lead to the failure of relationship and divorce. The present study aimed to investigate the effectiveness of schema therapy and emotional self-regulation therapy in the components of marital conflict in women referred to the psychological centers of Ahvaz City. Methods: It was a quasi-experimental study with a pre-test-post-test design and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2121
2121

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…comply with environmental differences and act flexibly in the face of differences (Chaves, Canavarro & Moura-Ramos 2019). Marital adjustment can help reduce marital conflicts and increase couples' adaptability by generating an evolutionary process in their relationships (Mohammadi et al 2020;Kroemeke & Kubicka 2018). This process can foster individuals' adjustment, adaptation, and transformation.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…comply with environmental differences and act flexibly in the face of differences (Chaves, Canavarro & Moura-Ramos 2019). Marital adjustment can help reduce marital conflicts and increase couples' adaptability by generating an evolutionary process in their relationships (Mohammadi et al 2020;Kroemeke & Kubicka 2018). This process can foster individuals' adjustment, adaptation, and transformation.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Emotional Schema Therapy (EST), as a novel approach to the treatment of emotional problems, is a socio-cognitive model of emotion and ER. This is because emotions are individual and a social phenomenon interpreted by oneself and others (Leahy 2019;Mohammadi et al 2020). In this model, individuals differ concerning the interpretations and assessments of their emotional experiences and may cope with their emotions by adopting different strategies, such as experiential avoidance,…”
Section: Introductionmentioning
confidence: 99%
“…Hemmati Sabet et al (20) demonstrated that employing cognitive therapy techniques helped patients learn to argue against incompatible perfectionism schemas and question their validity on a logical level. Furthermore, research findings suggest that the schema-based approach is effective for emotion regulation (21,22).…”
Section: Introductionmentioning
confidence: 99%